Curriculum policies for teacher training: disputes and negotiations in different contexts (Olhar de Professor, 2023)
This paper discusses the disputes and negotiations around curriculum policies for teacher education in Brazil. To this end, two contexts are analyzed from a documentary research based on curriculum theorists. The first is characterized by the 2014 National Education Plan (PNE), and the production of the production of the Resolution CNE/CP nº. 2/2015, and the second is marked by the impeachment process of 2016 and the consequent production of CNE/CP Resolution nº 2/2019 establishing BNC-Training. We interpret articulation processes and disputes between curricular projects of teacher training, involving different subjects and political and social demands. Finally, we defend the distinction between contexts, as well as the commitment to the permanence of political struggles as powerful in the disturbance of hegemonic stabilizations around curriculum policies for teacher training, especially those that are constituted in the current Brazilian political scenario.
Keywords: Curriculum Policies; Resolution CNE/CP nº. 2/2015.; BNC-Formation